Pulmonary Function Test: Spirometry. (March 2014) - Sewa, Duu Wen; Ong, Thun How
Spirometry is a useful tool in assessing the physiological lung function of a patient, and can be helpful in differentiating the etiology of the patient's symptoms. Indications for the test and the actual procedure are as described. Validity of a spirometry depends on patient co-operation and criteria for acceptability and repeatability must be met for useful interpretation of the results. Commonly measured parameters are described and a simple logarithm for interpretation of a spirometry result is given. Physicians must be mindful when interpreting the result in the context of extreme of ages, size or differing ethnicity as reference values for these groups of individuals are often extrapolated and not validated.